Overdrive pacing in the acute management of osimertinib-induced ventricular arrhythmias: A case report and literature review - Zhang, Yanyu; Wang, Xingtong; Pan, Yilin; Du, Beibei; Nanthakumar, Kumaraswamy; Yang, Ping (Frontiers in Cardiovascular Medicine, 2022)
QT interval prolongation and ventricular arrhythmias (VAs) induced by osimertinib, a third-generation epidermal growth factor receptor tyrosine kinase inhibitor, are life-threatening complications. However, no consensus has been achieved regarding their management. Overdrive pacing has been shown to be effective in shortening the QT interval and terminating torsade de pointes (TdP). Here, we report a case of osimertinib-induced QT prolongation accompanied by frequent VAs and TdP. Osimertinib was immediately discontinued after it was identified as the etiology for QT prolongation and VAs. A temporary pacemaker and overdrive pacing were used after other anti-arrhythmia treatments had failed and successfully shortened the QTc interval and terminated VAs. Repeated Holter monitoring at one week showed no remaining VAs or TdP, and the pacemaker was removed. Routine electrocardiography (ECG) surveillance was conducted afterward, and three- and six-month follow-ups showed good recovery and normal ECG results. Vigilance is required for rare vital arrhythmias in patients taking osimertinib, and ECG surveillance should be conducted.